2001
DOI: 10.1097/00005768-200103000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of two racing wheelchair propulsion techniques

Abstract: The greater push time and push angle associated with the PBT suggest that the PBT may be more suitable for endurance athletes who are less explosive in their pushing strokes. The greater time and angle allow PBT users the opportunity to transmit more force to the wheel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
2
13
0
3
Order By: Relevance
“…19 The corresponding impaired work capacity of SCI individuals compared to able-bodied persons can be attributed to the smaller active muscle mass available for physical performance. 20 It has been shown in SCI persons that the kind of sitting position 21 and the kind of upper body exercise 22 may influence muscle efficiency and force production during exercise. During handbike cycling, the athlete is sitting on a chair, the upper body is fixed on the bench and only the muscles of the shoulders and arms are mainly involved in exercise.…”
Section: Muscle Mass Involved In Exercisementioning
confidence: 99%
“…19 The corresponding impaired work capacity of SCI individuals compared to able-bodied persons can be attributed to the smaller active muscle mass available for physical performance. 20 It has been shown in SCI persons that the kind of sitting position 21 and the kind of upper body exercise 22 may influence muscle efficiency and force production during exercise. During handbike cycling, the athlete is sitting on a chair, the upper body is fixed on the bench and only the muscles of the shoulders and arms are mainly involved in exercise.…”
Section: Muscle Mass Involved In Exercisementioning
confidence: 99%
“…Although a number of studies have been conducted to examine the stroking characteristics of racing wheelchair propulsion (Higgs, 1986;Goosey et al, 1997Goosey et al, , 1998Goosey et al, , 2000Goosey-Tolfrey et al, 2001;Ridgway et al, 1988;Chow et al, 2000Chow et al, , 2001Cooper, 1990;Gehlsen et al, 1990;Maˆsse et al, 1992;O'Connor et al, 1998;Wang et al, 1995;Veeger et al, 1989;Woude et al, 1988), only one study has presented data related to wheelchair sprinting. Moss et al (2005) analyzed the first six strokes of a sprint start in over-ground racing wheelchair propulsion of an international male wheelchair athlete and concluded that ''racing wheelchair sprint propulsion is a complex form of locomotion and cannot be described accurately by using just the established definitions of a propulsive and a recovery phase.''…”
Section: Introductionmentioning
confidence: 99%
“…Manual wheelchair propulsion has been widely studied using 2D (Dallmeijer et al, 1994(Dallmeijer et al, , 1998Goosey and Campbell, 1998;Goosey et al, 2000;GooseyTolfrey et al, 2001;Veeger et al, 1992a, b, c) and 3D video analysis (Cooper et al, 1996(Cooper et al, , 1997Chow et al, 2000Chow et al, , 2001Kulig et al, 1998Kulig et al, , 2001Rodgers et al, 1994Rodgers et al, , 1998. All of the studies named above have simulated manual wheelchair propulsion in a laboratory environment using wheelchair ergometers (WERG's).…”
Section: Introductionmentioning
confidence: 99%